Se référer au passé pour faire du communalisme une alternative émancipatrice - Paula Cossart (Terrains/Théories, 2021)
We are interested here in libertarian writings that make the past a reserve of experiences likely to inspire a more just society, by focusing our attention on the valuations of the commune, understood as a grouping on a territorial basis of individuals self-managing in general assembly. We then question the writings of Murray Bookchin with a focus on the emancipatory role of real utopia, as put forward by Erik Olin Wright. Starting from the plea developed by the latter in favour of the adoption, by researchers in particular, of a posture of uncomplicated utopianism opening up the field of democratic possibilities, we question the relationship between anarchy, utopia and history, by analysing Bookchin's work in a new light. We begin by returning to the implications of Wright's posture : to make known the actual functioning of various alternative experiments, the social sciences being distinguished in this respect from purely imaginary utopian narratives. We then show that the relationship of some anarchist authors to utopia is close to this perspective. Based on an analysis of Bookchin's writings, we show that communalism constitutes a more powerful real utopia than those to which Wright refers. While Wright's approach is presentist, Bookchin's reference to the past allows him to go further. His view of history is rich in lessons for the development of a true democracy in the form of communalism today.